2024
DOI: 10.3233/jpd-230117
|View full text |Cite
|
Sign up to set email alerts
|

Delivering Multidisciplinary Rehabilitation Care in Parkinson’s Disease: An International Consensus Statement

Jennifer G. Goldman,
Daniele Volpe,
Terry D. Ellis
et al.

Abstract: Background: Parkinson’s disease (PD) is a complex neurodegenerative disorder impacting everyday function and quality of life. Rehabilitation plays a crucial role in improving symptoms, function, and quality of life and reducing disability, particularly given the lack of disease-modifying agents and limitations of medications and surgical therapies. However, rehabilitative care is under-recognized and under-utilized in PD and often only utilized in later disease stages, despite research and guidelines demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 206 publications
0
3
0
Order By: Relevance
“…It is stated, that in PD, cognitive and everyday functioning should be assessed and appropriate interventions initiated [33]. This is supported by a Global Consensus of Rehabilitation in PD, published in 2024 [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is stated, that in PD, cognitive and everyday functioning should be assessed and appropriate interventions initiated [33]. This is supported by a Global Consensus of Rehabilitation in PD, published in 2024 [8].…”
Section: Discussionmentioning
confidence: 99%
“…There is no medical cure for Parkinson's disease, and efforts that may improve quality of life and functional capacity in everyday life are therefore central to the management of the disease [1,3]. Efforts should include interventions targeting both motor and non-motor symptoms in general, as well as more specific problems caused by cognitive impairments [1,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Personalized exercise programs are feasible, accessible, and safe, as shown by Harpham et al [ 96 ] in a high-intensity interval training protocol in the home environment. A recent study [ 97 ] conducted by experts in multidisciplinary rehabilitation and PD found rehabilitation to be underutilized especially in early-stage PD and defined key principles for rehabilitative care. This, combined with our findings, could lead to PD treatment strategies shifting from more medication-focused towards exercise-focused, and we could see personalized exercise regiments becoming a more valuable tool for combating motor symptoms, especially in early PD.…”
Section: Future Directionsmentioning
confidence: 99%